Environmental Impact of Energy - Deded Chandra; Eri Barlian; Ali Amran (Science and Environmental Journal for Postgraduate, 2020)
The problems of energy, environment, and, global warming are becoming increasingly prominent in the era of globalization. Where the use of energy can pollute the environment due to the presence of solid waste, liquid waste, and pollutants due to emissions. Energy can change from one form to another, the changes often affect the environment and the air we breathe in various ways. Chemical energy in fossil fuels is converted into heat, mechanical, or electricity through combustion and this is the largest pollutant producer. And thus power plants, motor vehicles, and stoves are the main causes of air pollution. Issued pollutants are usually grouped into hydrocarbons (HC), nitrogen oxides (NOx), and carbon monoxide (CO). Pollutants produced in fossil burning are the biggest factors for smoke, acid rain, global warming, and climate change. If the situation cannot be managed properly, it will adversely affect the environment and also the survival of its inhabitants